Synthesis and Characterization of Phenothiazine‐Based Platinum(II)–Acetylide Photosensitizers for Efficient Dye‐Sensitized Solar Cells. Issue 11 (11th December 2015) - Siu, Chi‐Ho; Lee, Lawrence Tien Lin; Yiu, Sze‐Chun; Ho, Po‐Yu; Zhou, Panwang; Ho, Cheuk‐Lam; Chen, Tao; Liu, Jianyong; Han, Keli; Wong, Wai‐Yeung
Abstract: Three new unsymmetrical phenothiazine‐based platinum(II) bis(acetylide) complexesPT1 –PT3 with different electron‐donating arylacetylide ligands were synthesized and characterized. Their photophysical, electrochemical, and photovoltaic properties have been fully investigated and the density functional theory (DFT) calculations have been carried out. Under AM 1.5 irradiation (100 mW cm −2 ), thePT1 ‐based dye‐sensitized solar cell (DSSC) device exhibited an attractive power conversion efficiency ( η ) up to 5.78 %, with a short‐circuit photocurrent density ( J sc ) of 10.98 mA cm −2, an open‐circuit photovoltage ( V oc ) of 0.738 V, and a fill factor ( ff ) of 0.713. These findings provide strong evidence that platinum–acetylide complexes have great potential as promising photosensitizers in DSSC applications. Abstract : An attractive power conversion efficiency ( η ) of up to 5.78 %, a short‐circuit photocurrent density of 10.98 mA cm −2, an open‐circuit photovoltage of 0.738 V, and a fill factor of 0.713 are displayed by the newly synthesizedPT1 ‐based dye‐sensitized solar cell (DSSC, see figure) device. These findings provide strong evidence that platinum–acetylide complexes have great potential as promising photosensitizers in DSSC applications.